Russians in the jungle: Tubabao as a way station for refugees from China to Australia, 1949. Issue 4 (2nd October 2019) - Fitzpatrick, Sheila
Abstract: In 1949, Australia took in over 1300 'White Russians' … from China. They had been evacuated to the Philippines island of Tubabao by the International Refugee Organization (IRO) from Shanghai to escape the advancing Communists. This was a surprising move on Australia's part, given longstanding suspicions of Shanghai's Russian and Jewish community on grounds of immorality and political unreliability and the large-scale commitments Australia had already made to take 'displaced persons' from Europe in the wake of the Second World War to meet its labour shortages. Despite an avowed commitment to the strictest security and health vetting, Australia ended up accepting Russians from Tubabao – on average substantially older than its target migrant demographic, disinclined for manual labour and with a high incidence of TB – with only minimal security screening, despite widespread concerns that many held or had held Soviet passports. This article seeks to explain how this came about.